Exploring nurses' perceptions of the barriers and facilitators that influence acceptance and use of remote visual monitoring technology. (17th October 2022) - Hawksworth, Lisa T.; Raja, Sohayla; Drake, Jennifer; Davis, Theresa; O'Brien, Anne‐Marie; Brady, Joni M.
Abstract: Aim: Describe nurses' perceptions of the barriers and facilitators that influence acceptance and use of remote visual monitoring technology. Background: Research has shown remote visual monitoring to be a useful patient safety intervention, yet nurses underutilize the technology. Methods: Using a qualitative descriptive study design, we completed a conventional content analysis of focus group feedback from two nurse leader groups and two direct care nurse groups ( n = 13 participants) to explore factors influencing nurses' perceptions and utilization of remote visual monitoring. Results: Five main themes were identified: (1) Contextual human factors that impact nurse acceptance; (2) facilitators and barriers related to remote visual monitoring's functionality; (3) nurse leaders' role in maintaining device availability and efficient use; (4) nurse leaders' role in promoting adoption of the technology; and (5) nurse leaders' role in valuing nursing professional judgement. Conclusion: Findings indicate that nurse leaders can play a crucial role in direct care nurses' acceptance and use of remote visual monitoring technology. Implications for Nursing Management: In an era of limited staffing resources, remote visual monitoring has the potential to increase patient safety and decrease workload demands. Nurse leaders should identify barriers and facilitators to their nursing team's use of remote visual monitoring to promote the acceptance and use of technology that increases patient safety and cost‐effectiveness of care.